Helium atom in a box: a fully quantal solution - Mitnik, Dario Marcelo (2007)
A complete non-perturbative solution of the Helium atom in a box problem is presented by developing two numerical techniques. The first technique is the direct solution by diagonalization of the Hamiltonian, and the second is based on a constrained relaxation of the wave functions. Time-dependent propagation of doubly-excited wave-functions is analyzed, allowing the calculation and the visualization of the autoionization process.